Environmental attributes in assembling cyanobacterial communities from the Mcmurdo Sound region, Antarctica - Santos, Claudineia Lizieri dos (2014)
The variety of microbial ecosystems that exist in Antarctica represents an extraordinary opportunity for research on microbial ecology, diversity and evolution, particularly in terms of cyanobacteria. In this work we focus on the role of environment in controlling cyanobacterial mat assembly, and begin by describing the cyanobacterial diversity of mats along environmental gradients in the McMurdo Sound region, continental Antarctica. We then evaluated the role of environmental variables in determining their composition by analysing water and microbial cyanobacterial mat samples from 25 ponds from four distinct geographic sites: McMurdo Ice Shelf, Ross Island and Upper and Lower Wright Valleys. Finally we undertook a series of laboratory experiments to determine the extent to which species composition affects mat formation. Twenty nine morphospecies are identified and described in chapter one. Four were assigned to the order Chroococcales, three to the Nostocales and 22 to the Oscillatoriales. In chapter two, we investigated the factors that appeared to determine the presence or absence of morphospecies within the cyanobacterial mat community at each sampled pond. Ross Island, McMurdo Ice Shelf and Upper and Lower Wright Valleys ponds each showed some specific features in terms of physical-chemical factors and cyanobacteria diversity, though in many cases there was considerable overlap. Multivariate analysis based on physic-chemical variables showed that the ponds from each site tended to cluster by site, though with considerable overlap, and with the two Wright Valley and two coastal sites tending to be more similar to each other. This pattern tended to be reproduced in analysis of biomass and species composition data, and we were able to identify taxa that were broadly spread across the region and others that were more restricted by area. The importance of dispersal and growth conditions in driving this pattern is discussed. In chapter 3 we developed an experiment to evaluate the role of isolated cyanobacteria strains on the mat-building process. Six cyanobacteria strains, in varying combinations, were used to grow mats under laboratory conditions: CYN-50 (Phormidium cf. autumnale); CYN-68 (Leptolyngbya A); CYN-65 (Leptolyngbya B); CYN-66 (Microcoleus sp.); CYN-67 (cf. Aphanocapsa) and CYN-72 (Nostoc sp.). The content of chlorophyll-a, exopolysaccharide and organic matter was evaluated to assess mat development. At the end of our experiment, we observed that the mats developments showed variety in terms of their morphology, that oscillatorean cyanobacteria are required for coherent mat formation, but that different strains all produced effect mat matrices. P. autumnale produced the best developed mats. In conclusion, our findings provide an increased knowledge on the Antarctica cyanobacteria taxonomy and ecology in the McMurdo Sound region. We identified a mix of broadly tolerant, widely distributed organisms and other with more local distributions and specific environmental requirements. The significance of this in terms of management of Antarctic biodiversity is discussed.